Interaction of alpha-sarcin and gelonin with Cibacron blue. Issue 10 (October 1986) - Sperti, Simonetta; Montanaro, Lucio; Rambelli, Fioretta; Zamboni, Mariacristina
Abstract : Alpha-sarcin and gelonin, two proteins which inactivate the 60S ribosomal subunit, interact with Cibacron blue and bind to blue dextran-Sepharose, from which they are partially desorbed by nucleoside triphosphates and, more efficiently, by homopolynucleotides. It is further shown that the two proteins bind to poly(U)-Sepharose and that homopolynucleotides protect dilute solutions of both inhibitors from inactivation. It is suggested that the presence of a polynucleotide site on alphasarcin is related to its ribonuclease activity. The existence of a similar site on gelonin might be a clue to its yet unknown mechanism of action.